2008
DOI: 10.18433/j3sg66
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of amiodarone by various CYP isoenzymes of human and rat, and the inhibitory influence of ketoconazole

Abstract: -PURPOSE. To evaluate the metabolism of amiodarone (AM) to desethylamiodarone (DEA) by selected human and rat cytochrome P450, and the inhibitory effect of ketoconazole (KTZ). METHODS. Some important CYP isoenzymes (rat CYP1A1, 1A2, 2C6, 2C11, 2D1, 2D2, and 3A1 and human CYP1A1, 1A2, 2D6 and 3A4) were spiked with various concentrations of AM to determine the relative kinetic parameters for formation of DEA in the presence and absence of various concentrations of KTZ. RESULTS. The formation of DEA was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 34 publications
(49 reference statements)
2
50
0
Order By: Relevance
“…Our findings are in accordance with Korashy et al (Korashy et al, 2007) where ketoconazole was found to induce CYP1A1 at the transcriptional and protein level in human and murine cell lines. Others have found that ketoconazole is an effective CYP1A1 inhibitor in humans (Paine et al, 1999) and rats (Elsherbiny et al, 2008); our experiments are concordant, showing that ketoconazole is also a highly effective inhibitor of rabbit CYP1A1, in vitro. In our study, ketoconazole had opposite effects at the transcriptional and protein levels on CYP450 enzymes, in vitro.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings are in accordance with Korashy et al (Korashy et al, 2007) where ketoconazole was found to induce CYP1A1 at the transcriptional and protein level in human and murine cell lines. Others have found that ketoconazole is an effective CYP1A1 inhibitor in humans (Paine et al, 1999) and rats (Elsherbiny et al, 2008); our experiments are concordant, showing that ketoconazole is also a highly effective inhibitor of rabbit CYP1A1, in vitro. In our study, ketoconazole had opposite effects at the transcriptional and protein levels on CYP450 enzymes, in vitro.…”
Section: Discussionsupporting
confidence: 85%
“…A high ratio of DEA/aminodarone in the plasma and liver is considered as a risk factor for hepatotoxicity [54]. There is evidence demonstrating that CYP1A1 and CYP3A4 are the most efficient enzymes transforming amiodarone to DEA and the former isoform has higher potency [55], which is consistent with the results of our cytotoxicity assays. Several other CYP isoforms, including CYP1A2, CYP2C8, CYP2C19, and CYP2D6, have also been involved in DEA production in humans, but we found that the overexpression of these metabolizing enzymes did not increase but even decreased the cytotoxicity of amiodarone, suggesting that they may contribute, even more significantly, in the detoxification of DEA.…”
Section: Cytotoxic Effects Of Amiodaronesupporting
confidence: 88%
“…However, further studies are needed in order to confirm that this toxicity evaluation method can also be used to evaluate drugs with accumulative properties, like meloxicam (Seto et al, 2013;Türck et al, 1997), or that are degraded by metabolic enzymes, like amiodarones (Allen, 1993;Elsherbiny et al, 2008;Yonezawa et al, 2015). These drugs may affect the TK parameters throughout the dosing period, and may cause different phototoxic reactions between the first administration and final administration.…”
Section: Discussionmentioning
confidence: 99%